Analisa Strategi Pemasaran Penyewaan Gedung Kantor dengan Metode SWOT: Studi Kasus PT.Leads Property Service Indonesia - Anang Maulana (Jurnal Transformasi Bisnis Digital, 2024)
Leads Property Service Indonesia is a company operating in the services and services sector. PT. Leads Property Service Indonesia is widely known and many buildings use PT's services. Leads Property Service Indonesia for rent office space including the BRIpens Tower Building. To promote the office building area that will be rented only through the website so that there are problematic factors such as the lack of being able to go directly to provide brochures with clients because the website and social media promotions are more dominant and rental prices are less competitive with competitors in other companies. The solution is an evaluation so that it can become a future benchmark for marketing strategies for renting office buildings at the BRIPens PT Tower Branch Office. Leads Property Service Indonesia using the SWOT method. In essence, the SWOT method is a field of science that uses reasoning about the environment's internal strengths and weaknesses and also external opportunities and threats, then calculated using IFAS or EFAS using variables from these 4 parameters.